Polonovski-Type N-Demethylation of N-Methyl Alkaloids Using Substituted Ferrocene Redox Catalysts - Kok, Gaik B.; Scammells, Peter J. (Synthesis, 2012)
Various substituted ferrocenes have been trialed as catalysts in the nonclassical Polonovski reaction for N-demethylation of N-methyl alkaloids. Earlier studies suggest that conditions facilitating a higher ferrocenium ion concentration lead to superior outcomes. In this regard, the bifunctional ferrocene FcCH2CO2H, with electron donor and acceptor moieties in the same molecule, has been shown to be advantageous for use as a catalyst in the N-demethylation of a number of tertiary N-methylamines such as codeine, thebaine, and oripavine. These substrates are readily N-demethylated under mild conditions, employing sub-stoichiometric amounts of the substituted ferrocene at ambient temperature. These reactions are equally efficient in air and may also be carried out in one pot.
Keywords: N-demethylation; Polonovski reaction; substituted ferrocene; alkaloid